2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of EAC-ABET Program Criteria on Civil Engineering Curricula

Abstract: is Interim Dean of the College of Engineering and Computer Science at the University of Evansville. He earned his B.S. and Ph.D. degrees from the University of Missouri-Rolla and his M.S. degree in civil engineering from the University of Florida. He is a licensed professional engineer in California, Florida, Missouri, Illinois, and Indiana. He served on active duty in the Army (Officer-Corps of Engineers) and held positions as a senior civil engineer with a consulting firm and the director of Missouri's Dam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…ABET is slowly making changes to their course requirements (e.g. sustainability in design, public policy, leadership, and professional ethics) that have given engineering education programs greater flexibility in their curriculums-resulting in a measurable increase to the variability between programs (Swenty & Swenty, 2018). With these recent changes, institutions are better positioned to generate a curriculum that prepares students to meet changing societal demands (Bridges, 2000); however, just because a school may have additional flexibility to include ESJ in the curriculum, it is not clear whether individual institutions are motivated to elicit such a change in their curriculum.…”
Section: Mission Statements: a Bird's-eye View Of Engineering Culture...mentioning
confidence: 99%
“…ABET is slowly making changes to their course requirements (e.g. sustainability in design, public policy, leadership, and professional ethics) that have given engineering education programs greater flexibility in their curriculums-resulting in a measurable increase to the variability between programs (Swenty & Swenty, 2018). With these recent changes, institutions are better positioned to generate a curriculum that prepares students to meet changing societal demands (Bridges, 2000); however, just because a school may have additional flexibility to include ESJ in the curriculum, it is not clear whether individual institutions are motivated to elicit such a change in their curriculum.…”
Section: Mission Statements: a Bird's-eye View Of Engineering Culture...mentioning
confidence: 99%
“…As stated above, there is a large volume of competencies aligned with project management; however, there is no study that seeks to prioritize the competencies that should be developed in civil engineering degree programs. Indeed, many of the research carried out to state the skills and competencies that are fundamental for civil engineers, is focused in identifying the differences between the accreditation institutions criteria for the science and technology programs all over the world, and recognize if they are appropriate for the requirements of the 21st-century engineering [12]- [17]. The most cited accreditation institutions and boards, namely ABET, Accreditation Agency for Degree Programmes in Engineering, Informatics, Natural Sciences and Mathematics (ASIIN), American Society of Civil Engineers (ASCE), the European Network for Accreditation of Engineering Education (ENAEE), and Engineers Australia, have very similar criteria [16], in particular, those related to the student outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the average number of courses required and available in an undergraduate program, a student would graduate with the following NCSEA core structural engineering courses: 1. structural analysis I 2. steel I 3. reinforced concrete I 4. foundations However, in most cases, the first structural analysis course covers topics from both structural analysis I and II. Furthermore, previous research has shown that technical communication courses are required in approximately 50% of civil engineering undergraduate programs and as an elective in others [14]. Therefore, a reasonable assumption is that students will have taken 6 of 12 recommended core courses:…”
Section: Synthesis and Discussionmentioning
confidence: 99%